Cereal Processing By-Products as Rich Sources of Phenolic Compounds and Their Potential Bioactivities - Anca Fărcaș (MDPI AG, 2021)
In today’s society, we can see a progressive paradigm shift that tends towards a healthy and sustainable lifestyle. The proof is represented by the growing interest in food loss and waste of different sectors, from the political to the academic, or even to the private sector. In order to reduce food waste and to increase sustainability, the European Union (EU) has planned a circular bioeconomy. This action plan includes an approach based on reducing, reusing, recovering, and recycling materials and energy. Every year, there are high amounts of waste and by-products resulting from agricultural producing and agro-industrial processing, impacting the environment and the socio-economic sector. Cereal food products cover over 20% of daily diet, so it can be assumed that cereal production and processing are one of the most important sectors of agri-food industries. It is estimated that the waste generated from cereal processing and manufacturing is up to 13%, a percentage that can be decreased by converting the by-products in raw materials for biofuels, biodegradable plastics, alcohols, antioxidants, food additives, or pharmaceutic ingredients due to their content in macro- and micro-nutrients or bioactive compounds. Based on the fact that diet plays a crucial role in maintaining the integrity of our body, it is important to capitalize on any source of bioactive compounds to which we have access. This review aims to highlight the need to recirculate by-products for the purpose of extraction and use of their key compounds, polyphenols, which have not only antioxidant effects, but also preventive and therapeutic effects against cancer. For these, it is necessary to understand the biotechnologies needed for processing the most consumed cereals, the methods of extraction of phenolic compounds, and the main effects that these compounds have, summarizing the most relevant in vitro and in vivo studies performed so far.